2002
DOI: 10.3201/eid0812.020234
|View full text |Cite
|
Sign up to set email alerts
|

West Nile virus Epidemic in Horses, Tuscany Region, Italy

Abstract: During the late summer of 1998, veterinary authorities in Tuscany, Italy, received reports of cases of neurologic disease among horses residing in a large wetland area located in the provinces of Florence and Pistoia. West Nile virus was isolated from two of the six horses that died or were euthanized. A retrospective epidemiologic study identified 14 clinical neurologic cases that occurred from August 20 to October 6 (attack rate of 2.8%). A serologic survey conducted over a 700-km2 area in stables with and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
161
2
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(173 citation statements)
references
References 29 publications
9
161
2
1
Order By: Relevance
“…West Nile virus (WNV) is the cause of West Nile disease (WND), a re-emerging mosquito-transmitted disease of humans and animals [1,6,7,9,11,18]. In 1999, WNV was first detected in North America in New York, and subsequently the virus spread throughout Canada, the USA, Mexico and the Caribbean [13,14,21].…”
Section: Introductionmentioning
confidence: 99%
“…West Nile virus (WNV) is the cause of West Nile disease (WND), a re-emerging mosquito-transmitted disease of humans and animals [1,6,7,9,11,18]. In 1999, WNV was first detected in North America in New York, and subsequently the virus spread throughout Canada, the USA, Mexico and the Caribbean [13,14,21].…”
Section: Introductionmentioning
confidence: 99%
“…The activity in Italy during 1998 resulted in 14 horses displaying neurological signs. Follow up serological studies [5] revealed a 58% equine seroprevalence in the area of the outbreak, a far higher frequency than that for those with clinical signs. The clinical disease in horses described during the French outbreak in 2000 was in the Hérault and Gard department, close to where the outbreak in 1962-1963 occurred.…”
Section: Epidemiologymentioning
confidence: 99%
“…Although haemagglutination inhibition and complement fixation tests have been widely used in the past for the diagnosis of flavivirus diseases [64], including Japanese encephalitis in horses (Manual of Standards for Diagnostic Tests and Vaccines of the Office International des Épizooties, 2000), and these tests are available for WNV [5,72,73], they are not widely used for laboratory diagnosis of WNV infection in the horse as they are laborious, time-consuming, slow and cross-reactive with other flaviviruses. However, they can be valuable in areas free of circulating WNV-related flaviviruses and also have the advantage of being species-independent.…”
Section: Detection Of Antibodymentioning
confidence: 99%
“…Furthermore, abnormal behavior, dysmetria, teeth grinding, facial nerve paralysis and dysphagia have been observed as a result of brain damage due to WNV infection [3,25]. Cases of equine infection have been reported during epidemics, or outbreaks, of WNV in many countries, including Italy [1], France [16], Canada [26] and the United States [17], and thus WNV infection has become a major concern of the horse industry.…”
mentioning
confidence: 99%